Impact of single biochar application on maize growth and water-fertilizer productivity under different irrigation regimes - Yang, Wei; Feng, Gary; Jia, Yonglin; Yang, Yixuan; Gao, Xiaoyu; Gao, Lihua; Qu, Zhongyi (Frontiers in Plant Science, 2022)
The improvement of soil water and nutrient availability through soil management practices are crucial in promoting crop growth and obtaining high water-fertilizer productivity under limited irrigation. In this study, a 2×4 fully randomized factorial design with two drip-irrigation regimes and four biochar rates was performed during maize crop growing seasons for a semiarid region of China in 2015 and 2016. Irrigation regimes was applied on the basis of the water lower limit of -15 kPa soil matric potential as W15 and -35 kPa as W35. Maize straw-derived biochar application rate of 0 (B0), 15 (B15), 30 (B30), and 45 (B45) t ha-1 was once applied to sandy loam soil in the first growing season. Our results showed that the W15 and W35 regimes generally increased soil nutrient availability and organic matter content under all biochar treatment rates for the entire growth period. In comparison, the B45-induced increase in available P and K was higher in the W15 regime than in the W35 regime during the second growing season. Furthermore, biochar treatment improved the comprehensive fertility index (CFI), leaf area index, and yield of maize. Within the same biochar treatment, the CFI value was higher in the W15 regime than in the W35 regime during the first growing season. However, the opposite was observed in the second growing season. The average irrigation water productivity (IWP) increased by 11.6%, 8.8%, and 7.8% in the W35 regime and by 15.2%, 12.9%, and 10.2% in the W15 regime for the B15, B30, and B45 treatments, respectively. Moreover, biochar treatment enhanced maize grain yield and partial fertilizer productivity (PFP) of synthetic N, P, and K fertilizers under both irrigation regimes. The highest PFP values were observed in the B15 treatment under W15. In general, a one-time application of biochar treatment at a rate of 15 t ha-1 in the first growing season is recommended in terms of increasing the availability of N, P, K, and organic matter in sandy loam and also improve water-fertilizer productivity under irrigation water lower limit of -15 kPa soil matric potential.